(untitled) (Zien Journal of Social Sciences and Humanities, 2022)
This article analyses the concept of "mind", "mentality", "consciousness", "knowledge", "thought", "memory", "intellect" in English, and the opinions about them. In addition, definitions are compared with the Uzbek language.